Chapter The digitization of the private sector in the Italy. A non-aggregative method to monitor the NRRP agenda at macro-area level - Traversa, Susanna (Proceedings e report, 2023)
Covid-19 emergency has produced within societies a strong impulse toward digitization policies, designed to mitigate the negative effects produced on national economies and to ensure a recovery of it. Among the objectives included by the Italian Government within the National Recovery and Resilience Plan (NRRP) there is a boosting of investments in the 4.0 Transition with measures involving not only a strengthening of the digital infrastructure but also a greater diffusion of digital literacy among the population. Therefore, starting from the intervention forecasts contained within Mission 1, paragraph 2 "Digitization, innovation and competitiveness in the production system," four elementary indicators were selected from the I.Stat database in compliance with the requirements of data available from both a spatial and temporal standpoint. As a matter of fact, the study aims to trace and compare the performance obtained by the main Italian macro-areas from the point of view of digitization of the production system, considering the years preceding and concomitant to the COVID-19 pandemic. Due to the intrinsic complexity of the digitization phenomenon, the development of statistic measures to study it can be directed toward the construction of synthetic indices. Throughout the present study, a synthesis methodology has been adopted that takes advantage of a non-aggregative approach: the Partially ordered set (POSET). The study is divided into sections, in which the main opportunities related to the construction of an index that evaluates the performance of the policies presented in the RRP will be outlined, as well as the characteristics and implications attributable to the use of a non-aggregative approach such as the POSET in its declination for the temporal study of socio-economic phenomena, and lastly, a presentation will be made of the results obtained from the application of the index to the Italian context.